Sustained Improvements After Intervention to Prevent Contrast‐Associated Acute Kidney Injury: A Randomized Controlled Trial - Michael E. Matheny; Elizabeth Carpenter‐Song; Iben M. Ricket; Richard J. Solomon; Meagan E. Stabler; Sharon E. Davis; Lisa Zubkoff; Dax M. Westerman; Chad Dorn; Kevin C. Cox; Freneka F. Minter; Hani Jneid; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background In the IMPROVE AKI (A Cluster‐Randomized Trial of Team‐Based Coaching Interventions to Improve Acute Kidney Injury) trial, a combination of team‐based coaching and data‐driven surveillance dashboards reduced the odds of AKI following cardiac catheterization by 46%. The objective of this study was to determine if improvements in AKI outcomes would be sustained after completion of the active intervention. Methods and Results A 2×2 factorial cluster‐randomized trial with an 18‐month active intervention phase (October 2019–March 2021) and an 18‐month sustainability phase (April 2021–September 2022) conducted among cardiac catheterization laboratories in 20 Veterans Affairs sites. Interventions included team‐based coaching in a virtual learning collaborative or technical assistance, with and without access to an automated surveillance reporting dashboard. Data were collected on procedures involving adult patients undergoing diagnostic coronary angiography or percutaneous coronary interventions and not receiving chronic dialysis. The main outcome was AKI within 7 days of cardiac catheterization among all participants and those with preexisting chronic kidney disease. In addition, survey and focused interview data were collected to understand barriers and facilitators to sustaining AKI improvements. In this phase, 440 of 4160 patients experienced AKI, including 216 of 1260 patients with chronic kidney disease. Compared with technical assistance alone, we observed a reduction in AKI among virtual learning collaborative + automated surveillance reporting sites (adjusted odds ratio, 0.60 [95% CI, 0.42–0.86]). Sites had implemented standardized orders (11), oral and intravenous hydration standing orders (13), and contrast limiting protocols (10). Conclusions Team‐based coaching coupled with data‐driven surveillance dashboards reduced AKI by 40% during the 18 months after active participation in the trial. Process improvement education, care process standardization, and automated outcome feedback may be effective and durable methods for reducing AKI. Registration URL: https://clinicaltrials.gov/; Unique Identifier: NCT03556293.